Effect of treatment with human chorionic gonadotropin on day 5 after timed artificial insemination on fertility of lactating dairy cows - Nascimento, A B; Bender, R W; Souza, A H; Ayres, H; Araujo, R R; Guenther, J N; Sartori, R; Wiltbank, M C (Journal of dairy science, 2013)
Reproductive management programs that synchronize ovulation can ovulate a smaller than normal follicle, potentially resulting in inadequate progesterone (P4) concentrations after artificial insemination (AI). Ovulation of the dominant follicle of the first follicular wave with human chorionic gonadotropin (hCG) treatment can produce an accessory corpus luteum and increase circulating P4 concentrations. This manuscript reports the results of 2 separate analyses that evaluated the effect of hCG treatment post-AI on fertility in lactating dairy cows. The first study used meta-analysis to combine the results from 10 different published studies that used hCG treatment on d 4 to 9 post-AI in lactating dairy cows. Overall, pregnancies per artificial insemination (P/AI) were increased 3.0% by hCG treatment post-AI [34% (752/2,213) vs. 37% (808/2,184); Control vs. hCG-treated, respectively]. The second study was a field research trial in which lactating Holstein cows (n=2,979) from 6 commercial dairy herds were stratified by parity and breeding number and then randomly assigned to one of 2 groups: control (no further treatment, n=1,519) or hCG [Chorulon i.m.: 2,000 IU (in 3 of the herds) or 3,300 IU (in 3 herds); n=1,460] on d 5 after a timed AI (ovulation synchronized with Ovsynch, Presynch-Ovsynch, or Double-Ovsynch). In a subset of cows, the hCG profile and P4 changes were determined. Treatment with hCG increased P4 (4.3 vs. 5.3 ng/mL on d 12). Pregnancies per AI were greater in cows treated with hCG (40.8%; 596/1,460) than control (37.3%; 566/1,519) cows. Interestingly, an interaction among treatment and parity was observed; primiparous cows had greater P/AI after hCG (49.7%; 266/535) than controls (39.5%; 215/544). In contrast, older cows receiving hCG (35.7%; 330/925) had similar P/AI to controls (36.0%; 351/975).Thus, targeted use of hCG on d 5 after TAI enhances fertility about 3.0% (based on meta-analysis) to 3.5% (based on our field trial). Surprisingly, this fertility-enhancing effect of hCG was very large in first-lactation cows but not observed in older cows in the field study. Future research is needed to confirm these intriguing results and to determine why older cows did not have improved fertility after hCG treatment.